Quality of ‘Ponkan’ tangerines according to chemical thinning regularity - Moreira, Rodrigo Amato (2012)
Researches suggest that the chemical thinning with appropriate phytoregulators concentrations must be used for more than one year, in order to improve the quality of ‘Ponkan’ tangerines. Thus, the chemical thinning was applied for two years, in this study, in order to evaluate the physicochemical characteristics of ‘Ponkan’ (Citrus reticulata Blanco) tangerines. The evaluation process was conducted in a twelve-year-old tangerine orchard, grafted on ‘Rangpur’ lime (Citrus limonia Osbeck), spaced 6.0 m among rows and 3.0 m among plants. The plants were sprayed with four Ethephon concentrations (200 mg L-1, 400 mg L-1, 600 mg L-1 and 800 mg L-1), after the period of physiological fruit drop, when fruits reached 25-30 mm in transversal diameter, in January 2009 and January 2010. Plants without spraying were used as control. The experimental design was randomized blocks, with four blocks and four plants per plot. There was interaction between the Ethephon concentrations and years of thinning application for percentage of thinning, number of fruits, mass, transversal and longitudinal diameter, soluble solids contents, titritable acidity, ratio and total sugar. There was no effect of Ethephon concentrations for juice yield. The chemical thinning regularity with Ethephon application increased mass, transversal and longitudinal diameter, soluble solids and ratio of ‘Ponkan’ tangerines.